Effects of pre‐surgical nasoalveolar moulding on maxillary arch and nasal form in unilateral cleft lip and palate before lip surgery. (18th September 2017) - Fuchigami, T.; Kimura, N.; Kibe, T.; Tezuka, M.; Amir, M. S.; Suga, H.; Takemoto, Y.; Hashiguchi, M.; Maeda‐Iino, A.; Nakamura, N.
Structured Abstract: Objectives: To investigate the effects of pre‐surgical nasoalveolar moulding (PNAM) on the maxillary arch and nasal form in patients with unilateral cleft lip and palate (UCLP). Setting and Sample Population: This is a retrospective case series study. The subjects were infants with complete UCLP who were treated with PNAM (n = 18) at Kagoshima University Medical and Dental Hospital (Japan) between 2006 and 2013. Material and Methods: Maxillary dental casts and facial photographs were taken at the time of the first visit and immediately prior to lip surgery to evaluate the maxillary arch and nasal form changes. The dental casts were scanned with a laser scanner, and changes in the 3‐Dimensional coordinates of anatomical landmarks and alveolar cleft width were analysed. Moreover, we investigated the correlation between the changes in the maxillary alveolar arch and nasal form. Results: Regarding the maxillary alveolar arch form, the anterior points of the major segment had moved significantly to the cleft side just prior to the time of lip repair, and the alveolar cleft width was significantly decreased. For nasal form, the inclination and displacement of the columella were significantly improved. The improvement of columella inclination was moderately correlated with the posterior movement of the anterior points of the major segment. Conclusions: These findings indicate that PNAM for infants with UCLP enhanced symmetry in the maxillary alveolar arch and nasolabial form. In addition, the posterior movement of the anterior points of the maxillary alveolar arch was correlated with the improvement of columella deformation.